Multiple Targeting Approaches on Histamine H3 Receptor Antagonists - Khanfar, Mohammad A.; Affini, Anna; Lutsenko, Kiril; Nikolic, Katarina; Butini, Stefania; Stark, Holger (Frontiers in Neuroscience, 2016)
With the very recent market approval of pitolisant (Wakix®), the interest in clinical applications of novel multifunctional histamine H3 receptor antagonists has clearly increased. Since histamine H3 receptor antagonists in clinical development have been tested for a variety of different indications, the combination of pharmacological properties in one molecule for improved pharmacological effects and reduced unwanted side-effects is rationally based on the increasing knowledge on the complex neurotransmitter regulations. The polypharmacological approaches on histamine H3 receptor antagonists on different G-protein coupled receptors, transporters, enzymes as well as on NO-signaling mechanism are described, supported with some lead structures.